Community-Based Tourism: A Catalyst for Achieving the United Nations Sustainable Development Goals One and Eight - Leonard A. Jackson (Tourism and Hospitality)
Community-based tourism (CBT) is an innovative and participatory approach that places local communities at the center of tourism development. This model aligns with the United Nations Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty) and SDG 8 (Decent Work and Economic Growth). Through a synthesis of global case studies from regions such as Nepal, Kenya, Costa Rica, South Korea, and Zimbabwe, this paper examines the transformative potential of CBT in fostering inclusive economic growth, empowering marginalized communities, and promoting cultural and environmental sustainability. Content and comparative analyses reveal how CBT generates sustainable livelihoods, preserves cultural heritage, and addresses governance and dependency challenges. The study highlights interlinkages between SDGs 1 and 8 and provides actionable strategies for stakeholders, including policymakers, residents, tourists, and academics. Recommendations for addressing implementation barriers and future research directions underscore the need for innovative solutions, technological integration, and long-term community resilience planning. This paper affirms CBT’s role as a global model for sustainable tourism and equitable development.